Effects of antimicrobial peptide APSH‐07 on the growth performance, anti‐oxidation responses, stress resistance and intestine microbiota in large yellow croaker Larimichthys crocea. (20th December 2019) - Ge, Huaicheng; Wang, Qi; Chen, Hao; Liu, Guangxia; Pan, Ying; Chen, Jia; Zhang, Wenbing; Mai, Kangsen
Abstract: A 65‐day feeding trial was conducted to investigate the effects of dietary antimicrobial peptide APSH‐07 on the growth performance, anti‐oxidation responses, stress resistance and intestine microbiota of large yellow croaker Larimichthys crocea . Four isonitrogenous and isolipidic diets were formulated with 0, 30, 60 and 90 mg/kg of APSH‐07, respectively. The results showed that the fish fed with 90 mg/kg of dietary APSH‐07 had the significantly highest specific growth rate ( p  < .05). The activities of catalase, superoxide dismutase, the total anti‐oxidative capacity and lysozyme had the significantly highest values in liver of fish fed with 90 mg/kg of dietary APSH‐07 ( p  < .05). Serum glucose increased significantly in fish fed diets without APSH‐07 supplementation after temperature stress, while serum cortisol increased significantly in those after trawl stress ( p  < .05). Fish fed with 90 mg/kg of dietary APSH‐07 showed significantly higher operational taxonomic units, ACE estimator and phylogenetic diversity whole tree in intestine microbiota compared to fish fed without APSH‐07 ( p  < .05). In conclusion, under the present experimental condition, 90 mg/kg of antimicrobial peptide APSH‐07 supplementation in diet had the better growth performance, higher anti‐oxidation and stress resistance capacity, and a potentially more beneficial intestine microbial community of large yellow croaker.